Fabrication of a Biomimetic Hierarchical Surface Replicated from a Lotus Leaf and In Vitro Cellular Activities. Issue 2 (17th September 2014) - Lee, Jae Yoon; Lee, Hyeongjin; Kim, Yong Bok; Kim, Geun Hyung
Abstract Hierarchical surface structures have been used as tissue regenerative materials because they prompt an outstanding variety of cellular activities. Here, we sought to develop hierarchical structures on a poly(ϵ‐caprolactone) (PCL) surface to mimic the distinctive natural hierarchical structures of a lotus leaf using the two processes of micro/nano‐casting and plasma‐etching. The surface roughness was the micro‐ (3.01–3.07 μm) and nanoscales (97±16 nm). To observe the efficacy as a biomedical substrate, the surface was investigated on the cell metabolic and osteogenic differentiation. High cell viability (>2.9‐fold) and calcium deposition (>2.1‐fold) were observed on the surfaces versus the flat surfaces. From these results, we propose a new biomedical surface model that can induce high cellular activity at the cell‐surface boundary for regenerating bone and dental tissues.<inline-graphic xlink:href="ark:/27927/pgh3xrpf690" content-type="ppap201400076-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />